El Occidente bárbaro 400-1000 - Wallace-Hadrill, J. M. (John Michael) (In geardagum., 2014)
Professor Wallace-Hadrill traces the development of Western Europe from the dissolution of the late Roman Empire to the emergence, in the tenth century, of the individual states of medieval Europe.